Antara Yogyakarta dan Jakarta: Campur Kode dan Domestikasi Bahasa Jawa dalam Iklan Tokopedia - Munfa’ati Muadibah; Miranti Widyaningsih; Assolatu Jamiah; Asep Abbas Abdullah (SULUK: Jurnal Bahasa, Sastra, dan Budaya, 2020)
The sociolinguistic paradigm forms the background of this study. Code switching in advertisements is an interesting thing because it actually shows the interrelation between major and minor languages which are in Indonesian and Javanese. On the other hand, code switching is a linguistic phenomenon that is closely related to certain social situations. The object in this study is the Tokopedia advertisement "Berani Tentukan Mimpi: Lanjutkan Mimpi atau Ubah Mimpi". The method of the study is qualitative based on video advertisements in the Youtube channel. Based on the results of the analysis, it is concluded that the linguistic event (code switching) is Tokopedia's strategy in imaging itself, increasing the interest of producers and consumers in making transactions in the marketplace at once.